Long Memory and Parity Reversion in Real Exchange Rate (Malaysian Management Journal, 2003)
This paper examines the post Bretton Woods experience of the Malaysian Ringgit. In this period, Malaysia moved from a managed to a floating exchange rate environment.We examine persistence in real exchange rates by estimating fractionally integrated ARIMA models and find evidence of long memory, which induces persistence though this long memory need not be associated with a unit root. The results show that three out of four exchange rates being examined display mean reversion. The long memory process re-establishes the Purchasing Power Parity as a meaningful concept of long-run equilibrium relation between the exchange rate and relative prices.